Sistem Pengendalian Kecepatan Dua Motor Brushless DC (BLDC) dengan Nine Switch Inverter Menggunakan Metode PWM - Harahap, Charles R. (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
Abstract Two three phase inverters which consists of 12 switches are generally required to control two brushless DC Motors, which are complicated and inefficient to control them. One inverter has 6 switches. This research develops controlling of two brushless DC Motors using nine switch inverters with Pulse Width Modulation method. Nine switch inverter needs PWM for controlling frequency and voltage. Arduino is used to generate PWM in this research. Nine switch inverters are used to convert DC voltage to AC Voltage because of BLDC needs AC Voltage to drive the rotor of motors. In controlling two BLDC Motors, it includes switching control using PWM, to adjust the input frequency which then results in the effect of frequency on the voltage, current, speed of two BLDC Motors and torque. The test of this controller consists of the condition of the motor with and without load. The test results show that the speed of two BLDC motors can be controlled simultaneously with nine switch inverters by adjusting the input frequency. Keywords two brushless DC motors, nine switch inverter, pulse width modulation (PWM), Arduino, Simulink Matlab